Dysfunctional State and Human Rights Violations in Nigeria: An Assessment of President Buhari’s Administration (2015-2023) - Olusola Olasupo; Patrick Hosea; Babatunde Abioro (African Journal of Inter-Multidisciplinary Studies)
Human rights violations remain a historical issue. Thus, exploring this concern amidst the dysfunctionality of the state is more alarming considering that political terrain could serve as a breeding and conducive atmosphere for further human rights violations. This paper explores the nexus between the dysfunctionality of states and its implications on human rights violations in Nigeria. Using secondary data and thematic analysis, we more specifically focused on human rights violation cases in the two terms of office of President Mohammadu Buhari (2015- 2023). The paper explored the state of dysfunctionality and the violation of human rights during this period. The findings show there were violations of socio-economic and cultural rights, freedom of the press, freedom of movement, right to peaceful demonstration, and freedom of gathering and association, in Nigeria during President Buhari's administration. The paper concluded that for citizens’ rights to be adequately protected, the causal factors of a dysfunctional state must be addressed to avoid perverseness and continuous violation of human rights. Recommendations were made in favor of a newly negotiated social contract.